APLIKASI FUZZY PADA PERMASALAHAN PROGRAM TAK-LINIER - Wattimena, Abraham Z. (PATTIMURA UNIVERSITY, 2011)
One of the most purpose of non linear programing is to determine the optimal solution of its objective function. If the objective function of a certain non linear programing only possess a uniqe value function, it is easy to calculate its optimal solution. However, if the objective function of non linier programing possess multi functions, so there are two possibilities to determine their optimal solutions. Theses depend on whether there are conflic among them or not. In order to make them more easier, the fuzzy parameter could be applied to calculate the optimal solution.